(3GdESJKeGQ hGdJehjd hESJQGJjLjGJ JSYjQ GdChQGb GdeGdjI (B/s - (3YUQGf, YUQGf LdGds ((3GdEScfOQjI(B: s (3OGQ GdJYdje GdLGeYj(B, s, 2012)
(3CShGb GdChQGb GdeGdjI(B- (3GdJMdjd GdeGdj ddbhGFe GdeGdjI dGZQGV GdGSJKeGQ(B- (3GdJMdjd GdCSGSj aj GJNGP GdbQGQ GdGSJKeGQi(B- (3GdJMdjd Gdafj ddChQGb GdeGdjI(B- (3JMdjd YGFO heNGWQ GdChQGb GdeGdjI(B- (3eYGjjQ GNJjGQ GdCSge(B-(3MGdGJ JWHjbIs
Keywords: (3GdESJKeGQs; (3GdChQGb GdfbOjIs; (3GdJehjds